The Correlation of Light Chain 3B Immunohistochemical Expression with Histopathological Grading in Colorectal Adenocarcinoma - Fiandani, Fatma; Betty, Betty; Delyuzar, Delyuzar; Laksmi, Lidya Imelda; Lukito, Joko S. (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Colorectal cancer ranks third highest of all malignancies worldwide and ranks fourth out of the 10 most common cancers encountered in Indonesia. More than 90% of colorectal cancers are adenocarcinoma type. The mechanism of autophagy has a dual role in tumorigenesis, namely as a tumor suppressor and as a tumor promoter. Microtubule-associated protein 1 light chain 3B (LC3B) is one of the widely used autophagy markers. The role of autophagy requires further research so that LC3B can be considered as one of the predictors of prognosis, especially in colorectal adenocarcinoma. The aim of this research is to determine the correlation of Light Chain 3B immunohistochemical expression with histopathological grading of colorectal adenocarcinoma. Methods Cross-sectional analytic study of 41 samples diagnosed with colorectal carcinoma at H. Adam Malik General Hospital Medan. Staining was performed using a polyclonal antibody rabbit Light Chain 3B immunohistochemistry (GeneTex) which would appear positive in the cytoplasm of tumor cells at a dilution of 1: 500. LC3B expression was assessed semiquantitatively with low and high expression categories. Data analysis was tested with the Spearman correlation test. Results LC3B immunohistochemical expression has a very strong correlation with the histopathological grading of colorectal adenocarcinoma and in a positive direction where the higher the colorectal adenocarcinoma grade, the higher the LC3B immunohistochemical expression, and vice versa (p=0,0001; r=0,763). Conclusion There was a significant relationship between LC3B immunohistochemical expression and histopathological grading of colorectal adenocarcinoma.